STRATEGIC MANAGEMENT OF PROFESSIONAL COMPETENCY TEACHERS OF PRODUCTIVE COURSES IN SMK (Descriptive Study at Dinas Pendidikan Provinsi Jawa Barat, SMKN 1 Cimahi, and SMKN 3 Bandung) - Karnita; Sanusi, Achmad; Wasliman, Iim; Hanafiah (AGUSPATI Research Institute, 2021)
This research is motivated by the unfulfilled quantity and quality of productive subject teachers in SMK so that it affects the quality of graduates. The transfer of management of Vocational High Schools by Dinas Pendidikan since 2016 and Vocational Revitalization during 2015 – 2019 are interesting to study. This study aims to identify and analyze the application of strategic management principles in fostering the professional competence of productive subject teachers in SMK, which include: (1) environmental observation, (2) strategy formulation, (3) strategy implementation; and (4) evaluation and control. There are two theories used: (1) Strategic Management from Hunger and Wheelen (1996) and Coaching Theory programmed by Kemdikbudristek (2016). For the needs of this research, a qualitative approach and a descriptive method were chosen. The techniques used are interviews, observation, and documentation studies. The research locus is nas Pendidikan Provinsi Jawa Barat and SMK. The results of his research, in Dinas Pendidikan Provinsi Jawa Barat and SMKN have applied the principles of strategic management in fostering productive subject teachers. The indicators, (1) have carried out a SWOT analysis on environmental observations, (2) formulation of mission, goals, strategies, and policies; (3) has implemented the policy strategy, budget, and procedures; and (4) evaluation and control have been carried out although not yet effective. This stage tends to be neglected, partial, and poorly acted upon. Although it is considered ineffective, the results of developing the competence of productive teachers in SMK have begun to show positive implications for improving the quality of professional vocational productive teachers. The absorption of graduates and interest in SMK is increasing. The professional competence development carried out by Dinas Pendidikan Provinsi Jawa Barat and SMKN in their regions includes training, industrial internships, collaboration between vocational teachers and industrial practitioners, teacher welfare development, MGMP/KKG, independent learning, and PKG/PKB. Obstacles in the field include (a) complicated regulations and bureaucracy; (b) limited school budgets; (c) lack of management commitment; (e) The training is still general. The proposed alternative solutions are: (a) deregulation and debureaucratization; (b) increasing partnership with DUDI; (c) (d) optimization of PKG/PKB. The recommendations are (a) a competent team of experts in environmental analysis; (b) optimizing the implementation of teacher professional competence development; (c) optimization of control and assessment; (d) strengthen the managerial competence of principals; and (e) expand CSR with DUDI